Managing pain in prison: staff perspectives. Issue 3 (19th August 2014) - Walsh, Elizabeth; Butt, Christine; Freshwater, Dawn; Dobson, Rachael; Wright, Nat; Cahill, Jane; Briggs, Michelle; Alldred, David
Abstract : Purpose: This paper presents the findings of one part of a larger study, funded by the National Institute for Health Research, which explored the management of pain in adult male prisoners in one large category B prison in England. In this paper, we focus on the attitudes and perceptions of prison staff towards pain management in prison. Design/methodology/approach: A qualitative design was utilised to explore the staff perceptions of pain and pain management in one adult male prison. Questionnaires were provided for all staff with prisoner contact, and a follow up focus group was undertaken to further explore questionnaire data. Findings: The questionnaire and focus group findings demonstrated that staff had a good awareness of pain and pain management in prison, with both physical and emotional pain identified. The frequency of approaches by prisoners to staff for pain relief was noted to be high, whilst awareness of how the prison environment could potentially exacerbate pain was discussed. The acquisition of analgesia by prisoners for secondary gain was identified as a challenge to both assessing levels of pain and providing pain relief in prison, illustrating the complexity of providing care within a custodial culture. The effect on staff of caring for prisoners found to be confrontational and deceitful was significant for participants, with feelings of anger and frustration reported. Research limitations/implications: This study was undertaken in one adult male category B prison with a very high turnover of prisoners. Staff working in other types of prison, for example, higher security or those more stable with longer sentenced prisoners could provide alternative views, as may staff caring for younger offenders and women. The challenges to undertaking research in prison with staff who can understandably be reluctant to engage in reflection on their practice cannot be underestimated and impact significantly on available methodologies. Originality/value: This qualitative research is the first of its kind to offer the perspectives of both healthcare professionals and prison staff working with prisoners complaining of pain in an English prison. It provides the groundwork for further research and development.